Pengaruh Kepemimpinan Lee Kuan Yew dan FDI terhadap Peningkatan PDB per Kapita Singapura - Zulfiniar Nur Karimah; Shieny Tan Putri (Politeknik Kutaraja, 2021)
GDP per capita is the average value of every citizen’s income which is obtained by dividing the GDP value of a country with the amount of citizens it has. GDP per capita can be used as an indicator to assess whether a country is successful and performs well economic wise. In Southeast Asia, the country with the highest GDP per capita is Singapore. One of the driving factors for Singapore’s success was Lee Kuan Yew’s assertive and semi-authoritarian leadership style. This style of leadership allowed Lee Kuan Yew to build a strong initial foundation for Singapore’s economic growth. As the economy of Singapore grows the value of GDP per capita also increases. One of the other factors that contributed to the increasing value of GDP per capita is Foreign Direct Investment (FDI). FDI can increase capitals and assets owned by a country and create new jobs opportunity that can increase the citizens income and thus increasing the overall value of GDP and GDP per capita. So it makes sense that Singapore, the country with the highest GDP per capita value in Southeast Asia, also has the highest value of FDI inflows. The aims of this study is to analyze the the impact of Lee Kuan Yew’s leadership style and FDI toward the increasing value of Singapore’s GDP per capita value. From this analysis we have concluded that both Lee Kuan Yew’s leadership style and FDI inflows have positive impact toward the increase of GDP per capita.